The effects of traditional healing on HIV and AIDS management: An ethnographic study - Avhatakali A. Ndou-Mammbona (South African Family Practice)
Background: This article presents the effects of traditional healing on the management of human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) in the Vhembe district, South Africa. The Vhembe district is one of the rural districts in Limpopo Province, South Africa, in which traditional healers are used as the first point of consultation for most ailments, regardless of their causes.